Realization of high-speed adaptive quantum state estimation. (17th June 2019) - Nohara, Saki; Okamoto, Ryo; Yamagata, Koichi; Fujiwara, Akio; Takeuchi, Shigeki
Abstract: Adaptive quantum state estimation (AQSE) provides the best possible estimation of unknown parameters of quantum states. In implementations of AQSE, half wave plates (HWPs) driven by mechanical rotators are used to change the measurement basis, but these significantly limit the overall speed of the system. Here we report an AQSE system using a liquid crystal retarder (LCR). With precise calibration, the phase accuracy of an LCR can be below 3.6 × 10 −3 radians and as low as 1.2 × 10 −3 radians. Using an LCR, the time required to change the measurement basis is approximately 30 times smaller than for a system using an HWP, and the total time of AQSE is reduced by a factor of 5.